LIBS applicability for investigation of re-deposition and fuel retention in tungsten coatings exposed to pure and nitrogen-mixed deuterium plasmas of Magnum-PSI. (30th July 2021) - Jõgi, I; Paris, P; Piip, K; Ristkok, J; Talviste, R; Piirsoo, H-M; Tamm, A; Grigore, E; Hakola, A; Tyburska-Pueschel, B; van der Meiden, H J
Abstract: We have investigated the applicability of Laser Induced Breakdown Spectroscopy (LIBS) for analyzing the changes in the composition and fuel retention of W and W-Ta coatings following exposure to D2 or mixed D2 -N2 plasma beams in the linear plasma device Magnum PSI. The exposed samples were characterized by in situ ns-LIBS and complementary analysis methods Secondary Ion Mass Spectroscopy, Energy Dispersive x-ray spectroscopy and Nuclear Reaction Analysis. In agreement with the used complementary analysis methods, LIBS revealed the formation of up to 400 nm thick co-deposited surface layer in the central region of the coatings which contained a higher concentration of the main plasma impurities, such as N, and metals, such as Ta and Mo, the latter originating mainly from the substrate and from the plasma source. The deuterium retention on the other hand was highest outside from the central region of the coatings.